New approaches to the synthesis of sildenafil analogues and their enzyme inhibitory activity - Mojzych, Mariusz; Karczmarzyk, Zbigniew; Wysocki, Waldemar; Ceruso, Mariangela; Supuran, Claudiu T; Kryštof, Vladimir; Urbańczyk-Lipkowska, Zofia; Kalicki, Przemysław (Bioorganic & medicinal chemistry, 2015)
In the search for new biologically active chemotypes, several sildenafil analogs were prepared and characterized. The presence of the pyrazolo[4,3-e][1,2,4]triazine core is thought to be of interest for the enzyme inhibitory activity of these compounds. The designed derivatives incorporating the sildenafil scaffold were assayed as carbonic anhydrase inhibitors, and for their cytotoxic activity against MCF-7 and K562 cell lines. The X-ray analysis of one of these model compounds was performed and its crystal structure is described/compared to that of sildenafil.
Keywords: Enzyme Inhibitors; Pyrazolo[4,3-e][1,2,4]triazine; inhibitory enzymů; Phosphodiesterase 5 Inhibitors; DFT calculations; lidé; Crystallography, X-Ray; inhibitory fosfodiesterasy 5; MCF-7 Cells; MFC-7 buňky; Sildenafil analogues; Humans; Sulfonamides; X-ray structure analysis; krystalografie rentgenová; Sildenafil Citrate; K562 Cells; buňky K562; sildenafil citrát